PENGEMBANGAN MODUL PEMBELAJARAN DENGAN PENDEKATAN DISCOVERY LEARNING PADA MATERI LIMIT FUNGSI ALJABAR KELAS X DI SMA INSAN CENDEKIA SUKOHARJO TAHUN AJARAN 2015/2016 - Wulandari, Setyati Puji; Budiyono, Budiyono; Slamet, Isnandar (Journal of Mathematics and Mathematics Education, 2017)
Abstract: The aims of this research were to: 1) determine the validity of the results of the development of learning modules with discovery learning approach on the material of limit algebra functions; 2) determine the practicality of the development of learning modules; 3) determine the effectiveness of the development of learning modules; 4) determine whether students achievement in the material of limit algebra functions using learning modules is better than the students who don’t use it. The development of the modules was done through the modified Four D, namely define, design, development, and disseminate. Data were analyzed using descriptive analysis. Validity analysis was based on an expert assessment. Practicality analysis was based on implementation of learning module. Effectiveness analysis was based on student response after using the module. Analysis of student achievement was based on t-test hypothesis. The result concluded that: 1) learning modules with discovery learning approach to the material limit algebra functions declared fit for use by experts with the validity score of 3.44 and be in very good criteria; 2) learning modules expressed practical use in learning with the practicality score gained from the sheet of implementation of learning is 0.919 and be in very good criteria; 3) learning modules is effective for use in learning with the scores of effectiveness obtained from the sheet of student's response to the module is 3.03 and be in good criteria; 4) learning achievement of students who use the learning module is better than students who don’t use it, but isn’t significant.Keywords: learning module, discovery learning, limit algebra functions.